Long-acting anti-aging high-bonding-strength elastic hybrid adhesive as well as preparation method and application thereof

By adopting a ternary hybrid system in MS system adhesives, introducing acrylic modified MS and epoxy systems, and combining acidic pH adjusters and deionized water, the shortcomings of existing MS system adhesives in terms of storage stability, strength and elasticity are solved, and efficient and low-cost adhesive preparation is achieved, which is suitable for a variety of industrial applications.

CN119859500AActive Publication Date: 2025-04-22GUANGZHOU BLUOSHEN NEW MATERIAL TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510261529.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-22
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

The existing MS system adhesives have shortcomings in terms of storage stability, strength and elasticity, and cannot be stored stably for a long time and have high costs, which limits the further promotion of their applications.

Method used

Using a ternary hybrid system, through synchronous improvement of the adhesive formulation and process, an acrylic modified MS and epoxy system was introduced, combined with acidic pH adjuster and deionized water, compatibility and hydrolysis problems were overcome, and AB components that were stored in long-term and stable for a long time were prepared.

Benefits of technology

It realizes the high strength, high elasticity, high storage stability and low cost of the adhesive, and can obtain a glue layer with a large improvement in structural compactness, sealing and moisture and heat resistance after curing, meeting the needs of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859500A_ABST
    Figure CN119859500A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesive manufacturing, and discloses a long-acting anti-aging high-bonding-strength elastic hybrid adhesive as well as a preparation method and application thereof, and the preparation method of the adhesive comprises the following steps: preparing a long-acting component A of which the whole system is weakly acidic and has high storage stability, and preparing a long-acting component B of which the storage stability is high; the adhesive formula and the process are synchronously improved, a ternary hybrid system is adopted, the problems of compatibility of a ternary system, hydrolysis of an MS catalyst and the like are solved, and the prepared A component and the prepared B component can be stably stored for a long time, so that the adhesive has high strength, high elasticity, high storage stability and low cost at the same time; and the material is convenient to produce, can be stably stored for a long time, can be widely applied to manufacturing of products such as power battery cells and the like, and can meet various practical application requirements in the industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive manufacturing, and specifically relates to a long-lasting anti-aging high-bonding-strength elastic hybrid adhesive, a preparation method and application thereof. Background Art

[0002] MS adhesive, also known as silane-modified polyether adhesive, is an adhesive made of MS polymer as the base polymer, combined with fillers, plasticizers and other functional additives. At present, adhesives prepared with silane-modified polymers (MS resins) as the base raw materials, such as MS sealants or MS hybrid structural adhesives, are increasingly widely used due to their good adhesion to a variety of substrates, excellent elasticity and good strength. However, due to the widespread problems of hydrolysis (poor storage stability), poor mechanical properties and high cost of MS adhesives, their further promotion is limited. In particular, it should be pointed out that MS adhesives cannot simultaneously take into account high strength, high elasticity, and long-term storage stability (i.e., high storage stability), and conventional technologies cannot solve this problem.

[0003] For example, Chinese patent publication No. CN112552870A discloses a high-strength and high-hardness UV / moisture dual-curing MS glue and a preparation method thereof, which adopts a single component composed of high modulus silane-modified polyether polymers, etc. to solve the problem of poor strength of traditional MS glue; CN111732933A discloses a high-strength and high-hardness epoxy-modified MS sealant and a preparation method thereof, which introduces an epoxy system or an acrylic system into the MS system to improve strength and hardness. The above two technologies increase the strength of the material while also increasing the hardness of the colloid and decreasing its elasticity. They are not suitable for bonding and sealing application scenarios with high requirements such as vibration and thermal expansion and contraction, and both are unable to overcome the problems of moisture absorption and hydrolysis during long-term storage and transportation and poor storage stability.

[0004] For another example, Chinese patent publication number CN109880569A discloses an epoxy resin modified MS sealant, which adopts a two-component, binary resin system, and a small amount of water is included in component B as a co-catalyst; in its individual specific embodiment (Example 2), a specific adhesive layer with superior strength and elasticity can be obtained, but this embodiment is a filler-free formula and is costly, and the performance of the adhesive layer prepared in Example 1 after adding fillers (the system is alkaline) is greatly reduced, and it is difficult to take into account both high strength and high elasticity; in addition, in the embodiments of this patent, when MS catalyst and deionized water are added to component B at the same time, although deionized water has a curing-promoting effect and can be used as a co-catalyst, because the MS catalyst is a substance that is extremely easy to hydrolyze, the catalyst will gradually decompose and become inactivated in the presence of water, and the hydrolysis rate is further accelerated in an alkaline system, so it cannot be stored stably for a long time. Actual test results show that its component B usually loses its catalytic activity after several weeks to several months under room temperature storage conditions, and loses most of its catalytic activity in just one day under high-temperature storage conditions of 50°C.

[0005] In current industrial applications, downstream customers of domestic adhesives usually have an inventory cycle of about 3 months, and overseas customers also need an additional 3 months or longer shipping cycle. At present, the shelf life of MS system adhesives is generally 3 to 4 months, and during storage, the performance of the adhesive will decline to varying degrees due to hydrolysis, forcing companies to use operational means to compress the inventory cycle or technical means to increase the amount of adhesive to achieve timely use when the adhesive performance is good, or to avoid product quality substandard due to performance degradation. However, these measures will lead to increased costs for enterprises and cannot meet the needs of the industry to reduce costs, increase efficiency and improve quality. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a long-lasting, anti-aging, high-bonding-strength elastic hybrid adhesive, a preparation method and an application thereof. By simultaneously improving the adhesive formulation and process, a ternary hybrid system is adopted, and the problems of compatibility of the ternary system and hydrolysis of the MS catalyst are overcome, so that the prepared AB components can be stored stably for a long time, so that the adhesive can simultaneously take into account high strength, high elasticity, high storage stability and low cost, is easy to produce and can be stored stably for a long time, so as to solve the above-mentioned technical problems.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is: A method for preparing a long-lasting anti-aging high-bonding-strength elastic hybrid adhesive comprises the following steps: S1: Preparation of component A According to the set ratio, add MS resin, acrylic modified MS resin, epoxy resin, plasticizer, filler, and thixotropic additive into a double planetary stirring disperser, stir evenly, evacuate, heat to 110-120°C, and obtain dehydrated material after constant temperature, high-speed dispersion stirring and dehydration; Keep the dehydrated material in vacuum, lower the temperature to below 30°C, add coupling agent and epoxy catalytic curing agent, stir evenly under normal pressure, continue to keep vacuum, heat to 90-100°C, and disperse and stir at a constant temperature and high speed to make the coupling agent fully react with the active groups of MS resin, acrylic modified MS resin, epoxy resin, filler, and thixotropic additive to obtain resin base material, and then cool to below 30°C; A pH adjusting agent solution with a pH value of no more than 2 prepared in advance by deionized water and an acidic pH adjusting agent is added to the resin base material, and after being stirred and dispersed uniformly under normal pressure, vacuuming and stirring at a low speed to remove bubbles, the mixture is taken out of the kettle and sealed and packaged to obtain a long-acting A component with a weakly acidic overall system and high storage stability; S2: Preparation of component B According to the set ratio, add MS resin, acrylic modified MS resin, plasticizer, filler, antioxidant and thixotropic agent into the double planetary stirring disperser respectively, stir evenly and then evacuate, heat to 110-120℃, stir and disperse at constant temperature and high speed to dehydrate, and obtain dehydrated material; The dehydrated material is cooled to below 30°C under vacuum, and then a dehydrating agent is added. After the materials are stirred and dispersed under normal pressure until the materials are evenly mixed, the vacuum state is maintained, a coupling agent, an epoxy catalytic curing agent, and an MS catalyst are added. After the materials are stirred and dispersed under normal pressure until the materials are evenly mixed, a vacuum is drawn, the materials are stirred at a low speed to remove bubbles, the materials are discharged from the kettle, and the materials are sealed and packaged to obtain a long-acting B component with high storage stability; S3: Mixing and curing Mix component A and component B in a volume ratio of 2:1 and apply the mixture on the surface of the substrate to be bonded to form an adhesive coating; The adhesive coating is cured at room temperature for not less than 5 days, or heated at 50°C for not less than 10 hours. The moisture in component A is continuously consumed during the curing process. After the curing is completed, a long-lasting hybrid adhesive layer with high strength, high elasticity and resistance to moisture and heat aging is obtained.

[0008] A long-lasting anti-aging high-bonding-strength elastic hybrid adhesive is prepared by the aforementioned preparation method.

[0009] An application of the aforementioned long-lasting anti-aging, high bonding strength elastic hybrid adhesive in the manufacture of power battery cells.

[0010] The long-lasting anti-aging high-bonding-strength elastic hybrid adhesive, preparation method and application thereof provided by the present invention have at least the following beneficial effects: 1. The present invention improves the adhesive formulation and process simultaneously, adopts a ternary hybrid system, and overcomes the compatibility of the ternary system, the hydrolysis of the MS resin and the MS catalyst, and other problems, so that the prepared AB components can be stored stably for a long time, so that the adhesive can take into account high strength, high elasticity, high storage stability and low cost at the same time, is easy to produce and can be stored stably for a long time, and after curing, a dense structure, sealing and moisture-heat aging resistance can be obtained. The adhesive layer is greatly improved to meet the actual application needs of the industry.

[0011] 2. The adhesive provided by the present invention has two components AB that cooperate with each other, and an acrylic system and an epoxy system are simultaneously introduced into the MS system. The reasonable proportions of the three systems are controlled by formula design, and the amount of filler added, the amount of pH adjuster added, and the amount of water added are controlled to solve the problems of material compatibility, anti-hydrolysis, and anti-delamination, and the problem that the high strength, high elasticity, high density, and resistance to moisture and heat aging of the adhesive layer after curing cannot be taken into account. Thus, a low-cost, easy-to-prepare, high bonding strength (9-14MPa), high tensile strength (10-15MPa) two-component MS hybrid adhesive system is provided, which has high elasticity (200%-500%) and a long stable storage period (more than 12 months).

[0012] 3. The two-component MS hybrid adhesive system provided by the present invention improves the long-term storage stability of the two-component MS hybrid adhesive by adjusting the proportions of the three systems and improving the corresponding catalysts and storage conditions, and introducing an acidic pH regulator and deionized water into component A. The performance of component A and component B remains basically unchanged after long-term storage at room temperature for 6 months, and the performance loss is less than 5% after storage for 12 months; the performance loss does not exceed 10% after high-temperature storage at 50°C for 30 days, which is within the range allowed by industrial applications; at the same time, since the deionized water provided can make the curing process occur evenly from the inside of the adhesive layer, the density and various properties of the cured adhesive layer are greatly improved. After long-term use, when the performance loss of the adhesive layer of the ordinary MS hybrid adhesive formula exceeds 60% after wet heat aging, the performance loss of the adhesive layer of the present invention does not exceed 20%.

[0013] 4. The technical solution adopted by the present invention is to simultaneously introduce acrylic modified MS and epoxy system into the MS system for hybridization, wherein component A is designed to contain MS resin, acrylic modified MS resin and epoxy resin, and deionized water, and is weakly acidic as a whole; component B is designed to contain MS resin and acrylic modified MS resin; the ratio of MS / acrylic modified MS / epoxy resin after the AB components are mixed is controlled by the formula design to obtain better material compatibility and comprehensive performance; at the same time, the three resins in component A are reacted with a coupling agent in advance to modify them and coat the filler to enhance the hybridization uniformity of the three systems of MS resin, acrylic modified MS and epoxy after the AB components are mixed and cured, and to avoid the reaction of the filler with the acidic pH adjuster during storage and transportation; based on the above multiple optimizations, the performance of the colloid after the final curing can simultaneously take into account high strength, high elasticity and resistance to moisture and heat aging.

[0014] 5. The present invention adopts the method of adding additional water to component A so that AB has the performance of rapid curing, deep curing and uniform curing after mixing. At the same time, water and acidic pH regulator are introduced into component A to make the overall system of component A weakly acidic, thereby preventing the MS catalyst and MS resin from being hydrolyzed when there is water in component A. At the same time, the weak acidity also inhibits the further cross-linking of MS resin during long-term storage and transportation, resulting in performance degradation.

[0015] 6. The two-component MS hybrid adhesive of the present invention improves the bonding strength (8-10MPa) of the MS two-component hybrid adhesive to different substrates by optimizing the performance of the acrylic system and the epoxy system. It can be widely used in a variety of substrates with different polarities, including metal materials such as aluminum and stainless steel, and a variety of plastics such as high-polarity plastics PVC and PA and low-polarity plastics PET, thereby meeting the industrial application requirements for bonding different materials.

[0016] 7. The application of the long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive provided by the present invention is used in the bonding and fixing of power battery cells. The high-strength and high-elastic adhesive layer obtained after curing can solve the problem of structural failure caused by damage to the adhesive layer under alternating working conditions such as battery vibration and thermal expansion and contraction; when used in the sealing of power battery modules, the higher structural density (sealing) and wet-heat aging performance of the adhesive layer after curing can effectively extend the life of the power battery pack and can synergistically improve the overall safety performance of the power battery pack. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope image of a cross section of the adhesive layer of Example 3 of the present invention at a scale of 20 μm after the adhesive is cured; Figure 2 This is a scanning electron microscope image of a cross section of the adhesive layer of Example 3 of the present invention at a scale of 4 μm after the adhesive is cured; Figure 3 This is a scanning electron microscope image of a cross section of the adhesive layer of Comparative Example 3 of the present invention at a scale of 20 μm after the adhesive is cured; Figure 4 This is a scanning electron microscope image of a 4 μm-scale cross-section of the adhesive layer of Comparative Example 3 of the present invention after the adhesive is cured. DETAILED DESCRIPTION

[0018] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Basic Example The preparation method of the long-lasting anti-aging high-bonding-strength elastic hybrid adhesive provided in this embodiment comprises the following steps: S1: Preparation of component A According to the set ratio, add MS resin (silane-terminated polyether resin), acrylic modified MS resin (acrylic modified silane-terminated polyether resin), epoxy resin, plasticizer, filler, and thixotropic agent into a double planetary stirring disperser, stir evenly, evacuate, heat to 110-120°C, and disperse and stir at a constant temperature and high speed to obtain dehydrated material; Keep the dehydrated material in vacuum, lower the temperature to below 30°C, add the coupling agent and epoxy catalytic curing agent, stir evenly under normal pressure, continue to keep the vacuum, heat to 90-100°C, and stir at a constant temperature and high speed to make the coupling agent fully react with the active groups of MS resin, acrylic modified MS resin, epoxy resin, filler, and thixotropic additive to obtain a resin base material, and cool to below 30°C; in this step, the coupling agent fully reacts with the active groups of MS resin, acrylic modified MS resin, epoxy resin, filler, and thixotropic additive after high-temperature dehydration in the previous step. Filler (nanocarbon After the water molecules adsorbed on the surface of the coupling agent (calcium hydroxide) or thixotropic additive (fumed silica) dissociate or are removed, the hydroxyl groups on the surface of the filler are exposed to the resin, and the active groups on the surface of the filler are mainly hydroxyl groups and modified ester groups; when the coupling agent is stirred at normal pressure, in the presence of trace amounts of water, some of the silanol groups of the coupling agent are hydrolyzed to form silanols, and some of the silanols are also condensed to form oligomeric silanes; the ester group improves the compatibility of the filler with the resin, and the unhydrolyzed coupling agent reacts with the silanol bonds in the oligomeric silane and the hydrolyzed silanols of the coupling agent, and then reacts with the hydroxyl groups on the surface of the filler to form a molecular modification layer on the surface of the filler, and the amino group at the other end of the coupling agent is exposed to the resin. The amino group can react with the epoxy group at one end of the epoxy resin, so that part of the epoxy resin forms a wrap around the filler, and 2,4,6-tris(dimethylaminomethyl)phenol also plays a catalytic role in this process. During the stirring process at normal pressure, the silaneoxy groups at the ends of some MS resins and acrylic modified MS resins are hydrolyzed under the catalysis of trace water and 2,4,6-tris(dimethylaminomethyl)phenol, and can react with the hydroxyl groups on the surface of the filler to form a wrapping of the filler; or condense with the partially hydrolyzed coupling agent, and at the same time, the other end amino group of the coupling agent condensed with it reacts with the epoxy group of the epoxy resin, so that the two resin molecules are partially cross-linked to form a larger polymer, forming a entanglement between the resin polymer and the resin molecules on the surface of the filler, further strengthening the resin wrapping of the filler surface.

[0020] A pH adjusting agent solution with a pH value of no more than 2 prepared in advance by deionized water and an acidic pH adjusting agent is added to the resin base material, and after being stirred and dispersed uniformly under normal pressure, vacuuming and stirring at a low speed to remove bubbles, the mixture is taken out of the kettle and sealed and packaged to obtain a long-acting A component with a weakly acidic overall system and high storage stability; The specific steps include: S1-1: Prepare according to the following mass proportions: 30-50 parts of MS resin; 5-30 parts of acrylic modified MS resin; 20-50 parts of epoxy resin; 0-15 parts of plasticizer; 5-25 parts of filler; 0-2 parts of thixotropic additive; 1-3 parts of coupling agent; 0.3-0.75 parts of epoxy catalytic curing agent; appropriate amounts of acidic pH adjuster and deionized water; S1-2: Preparation of dehydrated material: Add MS resin, acrylic modified MS, epoxy resin, plasticizer, filler, and thixotropic additive to a double planetary stirring disperser, stir for 30 minutes at normal pressure and 25°C, evacuate and maintain the vacuum degree ≤-95kPa, heat to 110-120°C, and dehydrate at a constant temperature and high-speed dispersion stirring for 2 hours to obtain a dehydrated material; S1-3: Mutual reaction: keep the vacuum degree of the dehydrated material at ≤-95kPa, lower the temperature to below 30°C, add coupling agent and epoxy catalytic curing agent to the dehydrated material, stir for 30 minutes at normal pressure, keep the vacuum degree at ≤-95kPa, heat to 90-100°C, and disperse and stir at a constant temperature and high speed to allow the coupling agent to react with the active groups of MS resin, acrylic modified MS resin, epoxy resin, and filler for 1.5 hours, so that the resin completely covers the surface of the filler to obtain a resin base material, keep the vacuum degree at ≤-95kPa, and lower the temperature to below 30°C; In this step, the coupling agent reacts with the active groups on the surface of the ternary resin and the filler to establish a strong physical-chemical connection between the resin and the filler, while making the polymer resin wrap the filler more uniformly and tightly. On the one hand, it can improve the strength of the glue layer after curing, and on the other hand, it can prevent the filler from reacting with the acidic pH adjuster during manufacturing and storage and transportation.

[0021] S1-4: Preparation of pH adjusting agent solution: Take 1.5-2.0 times the amount of excess deionized water required for the complete hydrolysis reaction of MS resin and coupling agent, dissolve an appropriate amount of acidic pH adjusting agent in deionized water, and obtain a pH adjusting agent solution with a pH of 1-2; the amount of water required for the complete hydrolysis reaction of MS resin and coupling agent can be calculated according to conventional techniques, such as according to the following formula:

[0022] Where: · M is the mass of MS resin (in kg) · S is the mass of the coupling agent (in kg) · T is the hydrolysis temperature (in °C) · t is the hydrolysis time (in hours) · w is the amount of water (in kg) required for complete hydrolysis.

[0023] The specific parameters in the above formula (such as 0.6 and 0.035) can be adjusted as needed.

[0024] S1-5: Adjust the pH of the system: Add a pH adjuster solution to the resin base material to make the system weakly acidic as a whole, and stir and disperse for 30 minutes under normal pressure; In this step, the filler has been pre-wrapped by the resin material and will basically not react with the acidic pH regulator. The acidic pH regulator is added to make the system weakly acidic. On the one hand, it is to prevent the MS catalyst and MS resin from hydrolyzing or pre-crosslinking during storage and transportation; the quantitatively added water is used for the curing of the MS resin after the AB components are mixed, and is completely consumed during the curing process, which can greatly improve the speed and effect of curing (to achieve deep and uniform curing); S1-6: Discharging: Vacuum and stir at a low speed to remove bubbles for 10 minutes, remove from the kettle and seal and package to obtain a long-acting component A that can be stored stably for a long time.

[0025] In this embodiment, water is added to component A, and the curing process is not affected by the humidity of the curing environment, and there is no need to deliberately control the humidity in the curing environment; an acidic pH regulator is introduced to make the system weakly acidic (pH is 5-6), thereby inhibiting the MS catalyst and MS resin in component A from hydrolyzing or further cross-linking in the presence of external moisture and during long-term storage and transportation, thereby causing the viscosity of the rubber to increase and the performance to decrease.

[0026] S2: Preparation of component B According to the set ratio, add MS resin, acrylic modified MS resin, plasticizer, filler, antioxidant and thixotropic agent into the double planetary stirring disperser respectively, stir evenly and then evacuate, heat to 110-120℃, stir and disperse at constant temperature and high speed to dehydrate, and obtain dehydrated material; The dehydrated material is cooled to below 30°C under vacuum, and then a dehydrating agent is added. After the materials are stirred and dispersed under normal pressure until the materials are evenly mixed, the vacuum state is maintained, a coupling agent, an epoxy catalytic curing agent, and an MS catalyst are added. After the materials are stirred and dispersed under normal pressure until the materials are evenly mixed, a vacuum is drawn, the materials are stirred at a low speed to remove bubbles, the materials are discharged from the kettle, and the materials are sealed and packaged to obtain a long-acting B component with high storage stability; The specific steps include: S2-1: Prepare according to the following mass proportions: 20-40 parts of MS resin; 5-45 parts of acrylic modified MS resin; 0-30 parts of plasticizer; 5-40 parts of filler; 10-25 parts of epoxy catalytic curing agent; 2-10 parts of antioxidant; 0.5-3 parts of water scavenger; 2-20 parts of coupling agent; 0-5 parts of thixotropic additive; 2-6 parts of MS catalyst; S2-2: Preparation of dehydrated material: Add MS resin, acrylic modified MS, plasticizer, filler, antioxidant and thixotropic agent to a double planetary stirring disperser respectively, stir for 30 minutes at normal pressure and 25°C, evacuate and keep the vacuum degree at ≤-95kPa, heat to 110-120°C, and stir and disperse at a constant temperature and high speed for 2 hours to obtain a dehydrated material, keep the vacuum degree of the dehydrated material at ≤-95kPa, and cool down to below 30°C; S2-3: Dehydration: Add dehydrating agent to the dehydrated material in vacuum state, stir and disperse for 10 minutes under normal pressure until the material is evenly mixed, evacuate and maintain the vacuum degree at ≤-95kPa, stir and disperse again for 10 minutes to fully remove water; S2-4: Additive mixing: Add coupling agent, epoxy catalytic curing agent and MS catalyst to the dehydrated material after water removal, stir and disperse for 5 minutes under normal pressure until the materials are evenly mixed, evacuate and maintain the vacuum degree at ≤-95kPa, and stir and disperse for 30 minutes; S2-5: Discharging: Vacuum and stir at low speed to remove bubbles for 10 minutes, remove from the kettle and seal and package to obtain a long-acting B component with stable storage; S3: Mixing and curing Mix component A and component B in a volume ratio of 2:1 and apply the mixture on the surface of the substrate to be bonded or in the gap between the bonding surfaces of two substrates to be bonded to form an adhesive coating; The adhesive coating is cured at room temperature for not less than 5 days, or heated at 50°C for not less than 10 hours. The water in component A is continuously consumed during the curing process. After the curing is completed, a long-lasting hybrid adhesive layer with high strength, high elasticity and resistance to moisture and heat aging is obtained. The specific steps include the following: S3-1: Mixing: Mix component A and component B in a volume ratio of 2:1 and apply the mixture on the surface of the substrate to be bonded or in the gap between the bonding surfaces of two substrates to be bonded to form an adhesive coating; S3-2: Curing: Cure the adhesive coating at room temperature of 15-35°C for 7 days, or heat at 50°C for 16 hours. During the curing process, the moisture in component A is continuously consumed. After curing, a long-lasting hybrid adhesive layer is obtained that does not contain free water molecules, has high strength and high elasticity, and is resistant to moisture and heat aging.

[0027] In the long-lasting hybrid adhesive layer after component A and component B are mixed and cured: The weight ratio of MS resin, acrylic modified MS resin and epoxy resin is (40-60):(10-40):(20-35), and the ratio of the total weight of MS resin and acrylic modified MS resin to the weight of epoxy resin is ≥2; In the total weight of MS resin and acrylic acid modified MS resin, the acrylic acid modified MS resin accounts for ≥ 20%; Filler mass ratio ≤20%; The mass ratio of MS catalyst is 1%-3% of the total of MS resin and acrylic acid modified MS; The mass ratio of epoxy resin curing agent is 15%-25% of epoxy resin; The deionized water in the pH adjuster solution is completely consumed in the curing reaction.

[0028] The MS resin is a silane-terminated polyether resin, specifically a mixture of one or more of SAX750, SAX400, SAX260, TUPS400T, TUPS303T, and TUPS350D from Zhonghua Resin; The acrylic modified MS resin is an acrylic modified silane terminated polyether resin, specifically a mixture of at least one or more of Zhonghua resin MA480, MA490, and MA602; The epoxy resin is E51 or E44; The MS catalyst is a mixture of one or more of stannous octoate, dibutyltin dilaurate, dioctyltin dilaurate, di-n-butylbis(acetylacetonato)tin and 1,3-dilauroyloxy-1,1,3,3-tetrabutylditinoxy (U-130), preferably U-130 from Nitto Chemical Industry Co., Ltd. The plasticizer is a polyether polyol with a molecular weight greater than 1000, such as PPG3000; The epoxy catalytic curing agent is 2,4,6-tris(dimethylaminomethyl)phenol or tert-butylphenol; The antioxidant is one of IRGANOX 1010, IRGANOX 1076 and IRGANOX 1135; The dewatering agent is a vinyl methoxysilane, specifically one of vinyl trimethoxy silane (A-171), methyl vinyl dimethoxy silane or vinyl tri (2-methoxyethoxy) silane; The coupling agent is an amino coupling agent, specifically a mixture of one or more of KH-540, KH-550, and KH-792; The filler is nano calcium carbonate, with an oil absorption value of ≤35±1mL / 100g and an average particle size of ≤100nm, specifically a mixture of one or more of CCS-18, CCS-25, and CCS-25i; The filler may further add reinforcing carbon black, preferably Cabot M570 or M460, and the amount of carbon black added shall not exceed 2 parts by weight; The thixotropic additive is one or a mixture of fumed silica or polyamide wax; The acidic pH regulator of component A is a weak acid soluble in water, specifically citric acid or succinic acid, and its addition amount is such that the pH of the pH regulator solution is 1-2, and the mass ratio is not more than 3% of the weight of the filler in component A.

[0029] A long-lasting anti-aging high-bonding-strength elastic hybrid adhesive is prepared by the aforementioned preparation method.

[0030] An application of the aforementioned long-lasting anti-aging high bonding strength elastic hybrid adhesive in the manufacture of power battery cells can be used as a structural adhesive or sealant to bond and seal the structural surface of the power battery cell substrate to be bonded.

[0031] The embodiment of the present invention focuses on the simultaneous improvement of the adhesive formulation and process, the use of a ternary hybrid system, and the simultaneous overcoming of the compatibility of the ternary system, the hydrolysis of the MS resin and the MS catalyst, and other problems, so that the prepared AB components can be stored stably for a long time, so that the adhesive can simultaneously take into account high strength (mainly contributed by epoxy resin and filler, etc.), high elasticity (mainly contributed by acrylic acid / MS resin, etc.), high storage stability (mainly contributed by high compatibility, weak acid system, etc.) and low cost (contributed by filler, etc.), is easy to produce and can be stored stably for a long time, and after curing, a dense structure, a greatly improved sealing and moisture-heat aging resistance can be obtained to meet the actual application needs of the industry.

[0032] The present invention is further described in detail below in conjunction with the accompanying drawings and a number of specific embodiments, comparative examples and test results.

[0033] Example 1 The long-lasting anti-aging high-bonding-strength elastic hybrid adhesive, preparation method and application thereof provided in this embodiment are specific implementations based on the basic embodiment, and the difference lies in that: The specific components and proportions of component A and component B in this example are shown in Table 1.

[0034] The preparation method of the long-lasting anti-aging high-bonding-strength elastic hybrid adhesive provided in this embodiment specifically comprises the following steps: S1: Preparation of component A S1-1: Prepared according to the following mass ratios: SAX750 (MS resin from Zhonghua) 45 parts; MA480 (MS resin modified by Zhonghua acrylic acid) 9 parts; epoxy resin E51 30 parts; plasticizer PPG3000 2 parts; filler CCS-18 nano calcium carbonate 8 parts; thixotropic additive fumed silica 1 part; KH540 coupling agent 2 parts; epoxy catalytic curing agent K54 (2,4,6-tris(dimethylaminomethyl)phenol) 0.45 parts; acidic pH adjuster is citric acid 0.16 parts, deionized water 1.5 parts; S1-2: Preparation of dehydrated material: Add MS resin (silane-terminated polyether resin), acrylic modified MS resin (acrylic modified silane-terminated polyether resin), epoxy resin, plasticizer, filler, and thixotropic agent to a double planetary stirring disperser, stir for 30 minutes at normal pressure and 25°C, evacuate and maintain the vacuum degree ≤-95kPa, heat to 110-120°C, and dehydrate at a constant temperature and high-speed dispersion stirring for 2 hours to obtain a dehydrated material; S1-3: Mutual reaction: keep the vacuum degree of the dehydrated material at ≤-95kPa, lower the temperature to below 30°C, add coupling agent and epoxy catalytic curing agent to the dehydrated material, stir for 30 minutes at normal pressure, keep the vacuum degree at ≤-95kPa, heat to 90-100°C, and disperse and stir at a constant temperature and high speed to allow the coupling agent to react with the active groups of MS resin, acrylic modified MS resin, epoxy resin, and filler for 1.5 hours, so that the resin completely covers the surface of the filler to obtain a resin base material, keep the vacuum degree at ≤-95kPa, and lower the temperature to below 30°C; S1-4: preparing a pH adjusting agent solution: taking deionized water twice the amount of water required for the complete hydrolysis reaction of the MS resin and the coupling agent, dissolving an appropriate amount of an acidic pH adjusting agent in the deionized water to obtain a pH adjusting agent solution with a pH of about 1.7; S1-5: Adjust the pH of the system: Add a pH adjuster solution to the resin base material to make the system weakly acidic as a whole, and stir and disperse for 30 minutes under normal pressure; S1-6: Discharging: Vacuum and stir at a low speed to remove bubbles for 10 minutes, remove from the kettle and seal and package to obtain a long-acting component A that can be stored stably for a long time.

[0035] S2: Preparation of component B S2-1: Prepared according to the following mass proportions: 30 parts of SAX750 (MS resin); 20 parts of MA480 (acrylic modified MS resin); 4 parts of PPG3000 plasticizer; 12 parts of CCS-18 nano calcium carbonate filler, 1 part of M570 carbon black; 12 parts of K54 (epoxy catalytic curing agent); 5 parts of IRGANOX 1010 antioxidant; 1 part of A171 desiccant; 8 parts of KH540 coupling agent; 1 part of polyamide wax SL thixotropic additive; 3 parts of U-130 MS catalyst; S2-2: Preparation of dehydrated material: Add MS resin, acrylic modified MS, plasticizer, filler, antioxidant and thixotropic agent to a double planetary stirring disperser respectively, stir for 30 minutes at normal pressure and 25°C, evacuate and keep the vacuum degree at ≤-95kPa, heat to 110-120°C, and stir and disperse at a constant temperature and high speed for 2 hours to obtain a dehydrated material, keep the vacuum degree of the dehydrated material at ≤-95kPa, and cool down to below 30°C; S2-3: Dehydration: Add dehydrating agent to the dehydrated material in vacuum state, stir and disperse for 10 minutes under normal pressure until the material is evenly mixed, evacuate and maintain the vacuum degree at ≤-95kPa, stir and disperse again for 10 minutes to fully remove water; S2-4: Additive mixing: Add coupling agent, epoxy catalytic curing agent and MS catalyst to the dehydrated material after water removal, stir and disperse for 5 minutes under normal pressure until the materials are evenly mixed, evacuate and maintain the vacuum degree at ≤-95kPa, and stir and disperse for 30 minutes; S2-5: Discharging: Vacuum and stir at low speed to remove bubbles for 10 minutes, remove from the kettle and seal and package to obtain a long-acting B component with stable storage.

[0036] S3: Mixing and curing S3-1: Mixing: Component A and component B are mixed evenly in a volume ratio of 2:1. After the AB components are mixed, the weight ratio of MS resin, acrylic modified MS resin, and epoxy resin is 55:17:28. The mixed adhesive is coated on the surface of the substrate to be bonded, or in the gap between the bonding surfaces of two substrates to be bonded, to form an adhesive coating; S3-2: Curing: Cure the adhesive coating at room temperature of 15-35°C for 7 days, or heat at 50°C for 16 hours. During the curing process, the moisture in component A is continuously consumed. After curing, a long-lasting hybrid adhesive layer is obtained that does not contain free water molecules, has high strength and high elasticity, and is resistant to moisture and heat aging.

[0037] Example 2 The long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive, preparation method and application thereof provided in this embodiment are basically the same as those in Example 1, except that the formula components, proportions and preparation process of the long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive provided in this embodiment are slightly different.

[0038] When preparing component A in step S1, S1-1 is: Prepared according to the following mass proportions: SAX750 (Kaneka MS resin) 45 parts; MA480 (Kaneka acrylic modified MS resin) 10 parts; epoxy resin E51 25 parts; plasticizer PPG3000 8 parts; filler CCS-25 calcium carbonate 5 parts; KH540 coupling agent 1 part; K54 (epoxy catalytic curing agent 2, 4, 6-tris (dimethylaminomethyl) phenol) 0.38 parts; acidic pH adjuster is citric acid 0.1 parts, deionized water 1.5 parts, the pH value of the pH adjuster solution is about 1.8; When preparing component B in step S2, S2-1 is: Prepared according to the following mass proportions: 30 parts of SAX750 (MS resin); 6 parts of MA480 (acrylic modified MS resin); 10 parts of PPG3000 plasticizer; 6 parts of filler CCS-25 nano calcium carbonate and 1 part of M570 carbon black; 10 parts of K54 (epoxy catalytic curing agent); 4 parts of IRGANOX 1010 antioxidant; 2 parts of A171 desiccant; 12 parts of KH540 coupling agent; 0.7 parts of polyamide wax SL thixotropic additive; 2.6 parts of U-130 MS catalyst.

[0039] Example 3 The long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive, preparation method and application thereof provided in this embodiment are basically the same as those in Example 1, except that the formula components, proportions and preparation process of the long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive provided in this embodiment are slightly different.

[0040] When preparing component A in step S1, S1-1 is: Prepared according to the following mass proportions: SAX750 (Kaneka MS resin) 45 parts; MA480 (Kaneka acrylic modified MS resin) 26 parts; epoxy resin E51 44 parts; plasticizer PPG3000 12 parts; filler CCS-25i nano calcium carbonate 18 parts; KH540 coupling agent 3 parts; K54 (epoxy catalytic curing agent 2, 4, 6-tris (dimethylaminomethyl) phenol) 0.66 parts; acidic pH adjuster is citric acid 0.35 parts, deionized water 1.5 parts, the pH value of the pH adjuster solution is about 1.6; When preparing component B in step S2, S2-1 is: Prepared according to the following mass proportions: 30 parts of SAX750 (MS resin); 40 parts of MA480 (acrylic modified MS resin); 20 parts of PPG3000 plasticizer; 30 parts of CCS-25i nano calcium carbonate filler, 2 parts of M570 carbon black; 20 parts of K54 (epoxy catalytic curing agent); 7 parts of IRGANOX 1010 antioxidant; 2 parts of A171 desiccant; 12 parts of KH540 coupling agent; 1 part of polyamide wax SL thixotropic additive; 4.4 parts of U-130 MS catalyst.

[0041] Example 4 The long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive, preparation method and application thereof provided in this embodiment are basically the same as those in Example 1, except that the formula components, proportions and preparation process of the long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive provided in this embodiment are slightly different.

[0042] When preparing component A in step S1, S1-1 is: Prepared according to the following mass proportions: SAX750 (Kaneka MS resin) 15 parts; SAX400 (Kaneka MS resin) 15 parts; MA480 (Kaneka acrylic acid modified MS resin) 10 parts; MA490 (Kaneka acrylic acid modified MS resin) 10 parts; epoxy resin E51 30 parts; plasticizer PPG3000 5 parts; filler CCS-18 nano calcium carbonate 5 parts; thixotropic additive fumed silica 2 parts; KH792 coupling agent 2 parts; K54 (epoxy catalytic curing agent 2, 4, 6-tris (dimethylaminomethyl) phenol) 0.45 parts; acidic pH adjuster is citric acid 0.15 parts, deionized water 2 parts, to obtain a pH adjuster solution with a pH of about 1.8; When preparing component B in step S2, S2-1 is: Prepared according to the following mass proportions: SAX750 (Kaneka MS resin) 20 parts; SAX400 (Kaneka MS resin) 20 parts; MA480 (acrylic modified MS resin) 25 parts; MA490 (Kaneka acrylic modified MS resin) 20 parts; PPG3000 plasticizer 20 parts; filler CCS-18 nano calcium carbonate 38 parts, M570 carbon black 2 parts; K54 (epoxy catalytic curing agent) 25 parts; IRGANOX1010 antioxidant 5 parts; A171 desiccant 3 parts; KH540 coupling agent 20 parts; polyamide wax SL thixotropic additive 5 parts; U-130 MS catalyst 6 parts.

[0043] Example 5 The long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive, preparation method and application thereof provided in this embodiment are basically the same as those in Example 1, except that the formula components, proportions and preparation process of the long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive provided in this embodiment are slightly different.

[0044] When preparing component A in step S1, S1-1 is: Prepared according to the following mass proportions: SAX400 (Kaneka MS resin) 30 parts; MA480 (Kaneka acrylic acid modified MS resin) 15 parts; MA490 (Kaneka acrylic acid modified MS resin) 15 parts; epoxy resin E51 40 parts; plasticizer PPG3000 15 parts; filler CCS-18 nano calcium carbonate 20 parts; KH792 coupling agent 2 parts; K54 (epoxy catalytic curing agent 2, 4, 6-tris (dimethylaminomethyl) phenol) 0.60 parts; acidic pH adjuster is citric acid 0.4 parts, deionized water 3 parts, to obtain a pH adjuster solution with a pH of about 1.7; When preparing component B in step S2, S2-1 is: Prepared according to the following mass proportions: SAX400 (Kaneka MS resin) 40 parts; MA480 (acrylic modified MS resin) 5 parts; PPG3000 plasticizer 15 parts; filler CCS-18 nano calcium carbonate 19 parts, M570 carbon black 1 part; K54 (epoxy catalytic curing agent) 15 parts; IRGANOX 1010 antioxidant 5 parts; A171 desiccant 2 parts; KH540 coupling agent 10 parts; polyamide wax SL thixotropic additive 2 parts; U-130 MS catalyst 3 parts.

[0045] Example 6 The long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive, preparation method and application thereof provided in this embodiment are basically the same as those in Example 1, except that the formula components, proportions and preparation process of the long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive provided in this embodiment are slightly different.

[0046] When preparing component A in step S1, S1-1 is: Prepared according to the following mass proportions: SAX750 (Kaneka MS resin) 10 parts; SAX400 (Kaneka MS resin) 30 parts; MA490 (Kaneka acrylic modified MS resin) 20 parts; epoxy resin E51 50 parts; plasticizer PPG3000 10 parts; filler CCS-18 nano calcium carbonate 25 parts; KH792 coupling agent 2 parts; K54 (epoxy catalytic curing agent 2, 4, 6-tris (dimethylaminomethyl) phenol) 0.75 parts; acidic pH adjuster 0.4 parts of citric acid and 3 parts of deionized water, to obtain a pH adjuster solution with a pH of about 1.7.

[0047] When preparing component B in step S2, S2-1 is: Prepared according to the following mass proportions: SAX750 (Kaneka MS resin) 10 parts; SAX400 (Kaneka MS resin) 30 parts; MA490 (Kaneka acrylic modified MS resin) 20 parts; PPG3000 plasticizer 0 parts; filler CCS-18 nano calcium carbonate 4 parts, M570 carbon black 1 part; K54 (epoxy catalytic curing agent) 10 parts; IRGANOX 1010 antioxidant 5 parts; A171 desiccant 1 part; KH540 coupling agent 10 parts; polyamide wax SL thixotropic additive 2 parts; U-130 MS catalyst 3 parts.

[0048] Example 7 The long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive, preparation method and application thereof provided in this embodiment are basically the same as those in Example 1, except that the formula components, proportions and preparation process of the long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive provided in this embodiment are slightly different.

[0049] When preparing component A in step S1, S1-1 is: Prepared according to the following mass proportions: SAX750 (Kaneka MS resin) 35 parts; SAX400 (Kaneka MS resin) 15 parts; MA480 (Kaneka acrylic modified MS resin) 5 parts; epoxy resin E51 20 parts; plasticizer PPG3000 5 parts; filler CCS-18 nano calcium carbonate 10 parts; thixotropic additive fumed silica 1 part; KH792 coupling agent 1 part; KH540 coupling agent 1 part; K54 (epoxy catalytic curing agent 2, 4, 6-tris (dimethylaminomethyl) phenol) 0.30 parts; acidic pH adjuster is citric acid 0.2 parts, deionized water 2 parts, to obtain a pH adjuster solution with a pH of about 1.7; When preparing component B in step S2, S2-1 is: Prepared according to the following mass proportions: SAX750 (Kaneka MS resin) 15 parts; SAX400 (Kaneka MS resin) 5 parts; MA480 (acrylic modified MS resin) 25 parts; PPG3000 plasticizer 5 parts; filler CCS-18 nano calcium carbonate 5 parts, K54 (epoxy catalytic curing agent 5 parts); IRGANOX 1010 antioxidant 2 parts; A171 desiccant 0.5 parts; KH540 coupling agent 2 parts; U-130 MS catalyst 2 parts.

[0050] Example 8 The long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive, preparation method and application thereof provided in this embodiment are basically the same as those in Example 1, except that the formula components, proportions and preparation process of the long-lasting anti-aging, high-bonding-strength elastic hybrid adhesive provided in this embodiment are slightly different.

[0051] When preparing component A in step S1, S1-1 is: Prepared according to the following mass proportions: SAX750 (Kaneka MS resin) 15 parts; SAX400 (Kaneka MS resin) 35 parts; MA480 (Kaneka acrylic modified MS resin) 5 parts; epoxy resin E51 40 parts; plasticizer PPG3000 10 parts; filler CCS-18 nano calcium carbonate 10 parts; thixotropic additive fumed silica 1 part; KH792 coupling agent 2 parts; KH540 coupling agent 1 part; K54 (epoxy catalytic curing agent 2, 4, 6-tris (dimethylaminomethyl) phenol) 0.60 parts; acidic pH adjuster is citric acid 0.2 parts, deionized water 2 parts, to obtain a pH adjuster solution with a pH of about 1.7; When preparing component B in step S2, S2-1 is: Prepared according to the following mass proportions: 5 parts of SAX750 (Kaneka MS resin); 15 parts of SAX400 (Kaneka MS resin); 45 parts of MA480 (acrylic modified MS resin); 10 parts of PPG3000 plasticizer; 5 parts of filler CCS-18 nano calcium carbonate, 15 parts of K54 (epoxy catalytic curing agent); 2 parts of IRGANOX 1010 antioxidant; 0.5 parts of A171 desiccant; 10 parts of KH540 coupling agent; 3 parts of U-130 MS catalyst.

[0052] Table 1

[0053] Comparative Examples 1-3 The hybrid adhesives, preparation methods and applications provided in Comparative Examples 1-3 are substantially the same as those in Example 1, except that the specific materials and proportions of component A and component B are shown in Table 1, and the preparation steps are as follows: Preparation of component A: 1. Add MS resin (or acrylic modified MS), epoxy curing agent, plasticizer, filler, antioxidant, thixotropic agent to a double planetary stirring disperser, heat and vacuum, disperse and stir, maintain pressure ≤ -95kPa, heat and stir at 110-120℃, and disperse for 60-120min; 2. After the rubber material is cooled to below 30℃, add dehydrating agent and coupling agent, stir evenly, vacuum and stir for 30 minutes, and maintain the pressure ≤-95kPa 3. Vacuum and stir at low speed to remove bubbles for 10 minutes, then remove from the kettle and seal in plastic.

[0054] Preparation of component B: 1. Add epoxy resin, plasticizer and filler into the double planetary mixing disperser, vacuumize and disperse, and cool to below 30℃ 2. Add deionized water and stir for 30 minutes 3. Vacuum and stir at low speed to remove bubbles for 10 minutes. 4. Add the catalyst, stir evenly, vacuum and stir for 15-30 minutes, maintaining the pressure ≤-95kPa 5. Vacuum and stir at low speed to remove bubbles for 10 minutes, then remove from the kettle and seal in plastic.

[0055] Application Test Examples The two-component hybrid adhesives prepared in Examples 1-8 and Comparative Examples 1-3 were respectively applied to the manufacture of power lithium battery cells under the same conditions and tested after curing.

[0056] The performance test methods and steps are: 1. The two-component MS hybrid adhesives prepared in Examples 1-8 and Comparative Examples 1-3, component A and component B were mixed evenly in a volume ratio of 2:1, coated on the surface of a substrate of the same material to prepare a coating of the same thickness, placed at 25°C, 50% RH conditions for 7 days, and then tested.

[0057] 2. The tensile shear strength test is carried out in accordance with the national standard "GB 7124-2008 Determination of tensile shear strength of adhesives (rigid material to rigid material)", with a thickness of 0.2mm; the tensile strength and elongation at break are carried out in accordance with the national standard "GBT 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", and the comparative test results are shown in Table 2-3; 3. Storage stability test: Samples of component A and component B were plastic-sealed and stored in an oven at 50±2°C for 30 days, and then subjected to shear strength, tensile strength and elongation at break tests. The comparative test results are shown in Table 4.

[0058] Table 2

[0059] Table 3

[0060] Table 4

[0061] It can be seen from the comparative test data in Tables 2 to 4 above that the two-component MS hybrid adhesive provided in Examples 1-3 maintains high strength and high elasticity on the basis of adding fillers to reduce costs. When the strength is greater than 9MPa, the elongation at break is greater than 500%. When the bonding strength is further improved to greater than 14MPa, the elongation at break is still greater than 200%. Moreover, it maintains relatively high performance after wet heat aging and high-temperature storage. Comparative Examples 1-3 cannot maintain high strength and high elasticity at the same time, and the elongation decreases significantly after the strength is increased to 8MPa. The bonding strength of each embodiment to different substrates is also significantly higher than that of the comparative example.

[0062] See attached Figure 1-Figure 2(The cured adhesive layer of Example 3), the ternary hybrid adhesive system provided in Examples 1 to 8, by introducing acrylic modified MS resin, and at a set ratio of MS resin, acrylic modified MS resin, and epoxy resin, based on the characteristics that acrylic modified MS resin has relatively better compatibility with epoxy resin and is compatible with MS resin, can become a transition layer between two phase separation systems, making the microstructure after curing more uniform and dense, so that the cured adhesive layer will not have defects in the cured adhesive layer due to the phase separation of the epoxy system and the MS system, resulting in stress concentration, thereby improving the strength and density of the adhesive layer, thereby improving the sealing, and effectively reducing the infiltration of water molecules during wet heat aging. At the same time, the rigid epoxy resin cured segment and the acrylic resin cured segment can be evenly distributed in the MS system flexible segment, improving the colloid bonding strength and body strength while maintaining high flexibility.

[0063] See attached Figure 3-Figure 4 , the adhesive layer of comparative example 3 after curing, because the epoxy system and the MS system are not compatible, the two systems will form phase separation at the microscopic level after the colloid is cured, resulting in uneven microstructure of the adhesive layer. In each comparative example, when the proportion of acrylic modified MS and epoxy resin is increased, the bonding and bulk strength are improved, but because the proportion of MS resin system is too low, the rigid segment part will aggregate during curing, making the entire microstructure irregular; due to the higher polarity of the rigid segment, the macroscopic bonding and bulk strength are improved, but the irregular microscopic structure makes it easy for stress concentration to occur inside, resulting in a decrease in elongation at break. When subjected to vibration and thermal expansion and contraction of the bonding substrate, it is more likely to cause adhesive failure caused by adhesive layer damage.

[0064] The above embodiments of the present invention focus on hybridizing the three material systems (materials, proportions, processes, parameters) by constructing a ternary hybrid system (MS / acrylic modified MS / epoxy), and making the various parts cooperate with each other, and achieving performance balance by optimizing the AB component ratio. Acrylic modified MS and epoxy system are introduced into the MS system for hybridization at the same time, and the ratio of MS / acrylic modified MS / epoxy resin is optimized through a formula design different from the existing MS hybrid glue formula combination, so that the performance takes into account both high strength and high elasticity, and has good storage stability. In particular, through the synergistic effect of MS resin (improving elasticity), acrylic modified MS (improving bonding strength), and epoxy resin (improving rigidity); in view of the problems of MS catalyst hydrolysis and pre-crosslinking of MS resin, a formula design in which an acidic pH regulator and water coexist is adopted to effectively inhibit the pre-crosslinking of MS resin during storage and transportation, breaking through the limitation that traditional MS glue needs to be strictly waterproof, and greatly improving long-term storage stability. By pre-adding moisture to component A (rather than relying on ambient humidity), a controllable curing speed can be achieved, which promotes rapid and deep curing of the adhesive layer, increases the structural density of the adhesive layer, and ultimately results in a high-strength, high-elasticity, low-cost adhesive layer that is resistant to moisture and heat aging.

[0065] The long-lasting, anti-aging, high-bonding-strength elastic hybrid adhesive, preparation method and application thereof provided in the above-mentioned embodiments of the present invention provide a two-component MS hybrid adhesive that is easy to produce and has good storage properties through a new technical concept, and better solves the compatibility between different material systems, the problem of balancing high strength and high elasticity, and the problem that component A cannot be stored for a long period of time, and can meet various practical application needs of the industry.

[0066] It should be particularly pointed out that the components, proportions, particle sizes and process parameters used in the above-mentioned specific embodiments of the present invention are only examples. Other different implementation schemes obtained by making specific selections within the scope recorded in the basic embodiments of the present invention can achieve the technical effects recorded in the present invention, so the present invention will not list them one by one.

[0067] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. All equivalent changes made according to the components, proportions and processes of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a long-lasting anti-aging high-bonding-strength elastic hybrid adhesive, characterized in that: It at least includes the following steps: S1: Preparation of component A According to the set ratio, add MS resin, acrylic modified MS resin, epoxy resin, plasticizer, filler, and thixotropic additive into a double planetary stirring disperser, stir evenly, evacuate, heat to 110-120°C, and obtain dehydrated material after constant temperature, high-speed dispersion stirring and dehydration; Keep the dehydrated material in vacuum, lower the temperature to below 30°C, add coupling agent and epoxy catalytic curing agent, stir evenly under normal pressure, continue to keep vacuum, heat to 90-100°C, and disperse and stir at a constant temperature and high speed to make the coupling agent fully react with the active groups of MS resin, acrylic modified MS resin, epoxy resin, filler, and thixotropic additive to obtain resin base material, and then cool to below 30°C; A pH adjusting agent solution with a pH value of no more than 2 prepared in advance by deionized water and an acidic pH adjusting agent is added to the resin base material, and after being stirred and dispersed uniformly under normal pressure, vacuuming and stirring at a low speed to remove bubbles, the mixture is taken out of the kettle and sealed and packaged to obtain a long-acting A component with a weakly acidic overall system and high storage stability; S2: Preparation of component B According to the set ratio, add MS resin, acrylic modified MS resin, plasticizer, filler, antioxidant and thixotropic agent into the double planetary stirring disperser respectively, stir evenly and then evacuate, heat to 110-120℃, stir and disperse at constant temperature and high speed to dehydrate, and obtain dehydrated material; The dehydrated material is cooled to below 30°C under vacuum, and then a dehydrating agent is added. After the materials are stirred and dispersed under normal pressure until they are evenly mixed, the vacuum state is maintained, a coupling agent, an epoxy catalytic curing agent, and an MS catalyst are added. After the materials are stirred and dispersed under normal pressure until they are evenly mixed, a vacuum is applied, the materials are stirred at a low speed to remove bubbles, the materials are discharged from the kettle, and the materials are sealed and packaged to obtain a long-acting B component with high storage stability.

2. The method for preparing the long-lasting anti-aging high-bonding-strength elastic hybrid adhesive according to claim 1, characterized in that: It also includes the following steps: S3: Mixing and curing Mix component A and component B in a volume ratio of 2:1 and apply the mixture on the surface of the substrate to be bonded or in the gap between the bonding surfaces of two substrates to be bonded to form an adhesive coating; The adhesive coating is cured at room temperature for not less than 5 days, or heated at 50°C for not less than 10 hours. The moisture in component A is continuously consumed during the curing process. After the curing is completed, a long-lasting hybrid adhesive layer with high strength, high elasticity and resistance to moisture and heat aging is obtained.

3. The method for preparing the long-lasting anti-aging high-bonding-strength elastic hybrid adhesive according to claim 1 or 2, characterized in that: The step S1 specifically includes the following steps: S1-1: Prepare according to the following mass proportions: 30-50 parts of silane-terminated polyether resin; 5-30 parts of acrylic acid-modified silane-terminated polyether resin; 20-50 parts of epoxy resin; 0-15 parts of plasticizer; 5-25 parts of filler; 0-2 parts of thixotropic additive; 1-3 parts of coupling agent; 0.3-0.75 parts of epoxy catalytic curing agent; appropriate amounts of acidic pH adjuster and deionized water; S1-2: Preparation of dehydrated material: Add silane-terminated polyether resin, acrylic acid-modified silane-terminated polyether resin, epoxy resin, plasticizer, filler, and thixotropic additive to a double planetary stirring disperser, stir for 30 minutes at normal pressure and 25°C, evacuate and maintain the vacuum degree ≤-95kPa, heat to 110-120°C, and dehydrate at a constant temperature and high-speed dispersion stirring for 2 hours to obtain a dehydrated material; S1-3: Mutual reaction: keep the vacuum degree of the dehydrated material at ≤-95kPa, lower the temperature to below 30°C, add coupling agent and epoxy catalytic curing agent to the dehydrated material, stir for 30 minutes under normal pressure, keep the vacuum degree at ≤-95kPa, heat to 90-100°C, and disperse and stir at a constant temperature and high speed to allow the active groups of the coupling agent, MS resin, acrylic modified MS resin, epoxy resin, filler, and thixotropic additive to fully react for 1.5 hours, so that the resin completely covers the surface of the filler to obtain a resin base material, keep the vacuum degree at ≤-95kPa, and lower the temperature to below 30°C; S1-4: preparing a pH adjusting agent solution: taking deionized water 1.5-2.0 times the amount of water required for the complete hydrolysis reaction of the MS resin and the coupling agent, dissolving an appropriate amount of an acidic pH adjusting agent in the deionized water to obtain a pH adjusting agent solution having a pH value of no more than 2; S1-5: Adjust the pH of the system: Add the pH adjuster solution to the resin base material and stir and disperse for 30 minutes under normal pressure; S1-6: Discharging: Vacuum and stir at low speed to remove bubbles for 10 minutes, remove from the kettle and seal and package to obtain a long-acting component A that is stable in storage.

4. The method for preparing the long-lasting anti-aging high bonding strength elastic hybrid adhesive according to claim 1, characterized in that: The step S2 specifically includes the following steps: S2-1: Prepare according to the following mass proportions: 20-40 parts of MS resin; 5-45 parts of acrylic modified MS resin; 0-30 parts of plasticizer; 5-40 parts of filler; 10-25 parts of epoxy catalytic curing agent; 2-10 parts of antioxidant; 0.5-3 parts of water scavenger; 2-20 parts of coupling agent; 0-5 parts of thixotropic additive; 2-6 parts of MS catalyst; S2-2: Preparation of dehydrated material: Add MS resin, acrylic modified MS, plasticizer, filler, antioxidant and thixotropic agent to a double planetary stirring disperser respectively, stir for 30 minutes at normal pressure and 25°C, evacuate and keep the vacuum degree at ≤-95kPa, heat to 110-120°C, and stir and disperse at a constant temperature and high speed for 2 hours to obtain a dehydrated material, and keep the vacuum degree of the dehydrated material at ≤-95kPa and cool it down to below 30°C; S2-3: Dehydration: Add dehydrating agent to the dehydrated material in vacuum state, stir and disperse for 10 minutes under normal pressure until the material is evenly mixed, evacuate and maintain the vacuum degree at ≤-95kPa, stir and disperse again for 10 minutes to fully remove water; S2-4: Additive mixing: Add coupling agent, epoxy catalytic curing agent and MS catalyst to the dehydrated material after water removal, stir and disperse for 5 minutes under normal pressure until the materials are evenly mixed, evacuate and maintain the vacuum degree at ≤-95kPa, and stir and disperse for 30 minutes; S2-5: Discharging: Vacuum and stir at low speed to remove bubbles for 10 minutes, remove from the kettle and seal and package to obtain a long-acting B component with stable storage.

5. The method for preparing the long-lasting anti-aging high bonding strength elastic hybrid adhesive according to claim 2, characterized in that: The step S3 specifically includes the following steps: S3-1: Mixing: Mix component A and component B in a volume ratio of 2:1 and apply the mixture on the surface of the substrate to be bonded or in the gap between the bonding surfaces of two substrates to be bonded to form an adhesive coating; S3-2: Curing: Curing the adhesive coating at room temperature for not less than 5 days, or heating at 50°C for not less than 10 hours. During the curing process, the water in component A is continuously consumed. After curing, a long-lasting hybrid adhesive layer is obtained that does not contain free water molecules, has high strength and high elasticity, and is resistant to moisture and heat aging.

6. The method for preparing the long-lasting anti-aging high-bonding-strength elastic hybrid adhesive according to claim 5, characterized in that: In the long-lasting hybrid adhesive layer after component A and component B are mixed and cured: The weight ratio of MS resin, acrylic modified MS resin and epoxy resin is (40-60): (10-40): (20-35), and the ratio of the total weight of MS resin and acrylic modified MS resin to the weight of epoxy resin is ≥2; In the total weight of MS resin and acrylic acid modified MS resin, the acrylic acid modified MS resin accounts for ≥15%; Filler mass ratio ≤20%; The mass ratio of MS catalyst is 1%-3% of the total of MS resin and acrylic acid modified MS resin; The mass ratio of epoxy resin curing agent is 15%-25% of epoxy resin; The deionized water in the pH adjuster solution is completely consumed in the curing reaction.

7. The method for preparing the long-lasting anti-aging high-bonding-strength elastic hybrid adhesive according to claim 6, characterized in that: The MS resin is a silane-terminated polyether resin, specifically a mixture of at least one or more of SAX750, SAX400, SAX260, TUPS400T, TUPS303T, and TUPS350D from Zhonghua Resin; The acrylic modified MS resin is an acrylic modified silane terminated polyether resin, specifically a mixture of at least one or more of Zhonghua resin MA480, MA490, and MA602; The epoxy resin is E51 or E44; The MS catalyst is a mixture of at least one or more of stannous octoate, dibutyltin dilaurate, dioctyltin dilaurate, di-n-butylbis(acetylacetonato)tin and 1,3-dilauroyloxy-1,1,3,3-tetrabutylditinoxy; The epoxy catalytic curing agent is 2,4,6-tris(dimethylaminomethyl)phenol; The plasticizer is a polyether polyol having a molecular weight greater than 1000; The epoxy catalytic curing agent is 2,4,6-tris(dimethylaminomethyl)phenol or tert-butylphenol; The antioxidant is at least one of IRGANOX 1010, IRGANOX 1076 and IRGANOX 1135; The dewatering agent is a vinyl methoxysilane, specifically one of vinyl trimethoxy silane, methyl vinyl dimethoxy silane or vinyl tri (2-methoxyethoxy) silane; The coupling agent is an amino coupling agent, specifically at least one or more mixtures of KH-540, KH-550, and KH-792; The filler is nano calcium carbonate, with an oil absorption value of ≤35±1 mL / 100 g and an average particle size of ≤100 nm, specifically at least one or more mixtures of CCS-18, CCS-25, and CCS-25i; The thixotropic additive is one or a mixture of fumed silica or polyamide wax.

8. The method for preparing the long-lasting anti-aging high bonding strength elastic hybrid adhesive according to claim 6, characterized in that: The weight ratio of the MS resin, the acrylic modified MS resin, and the epoxy resin is 55:17:28; The acidic pH regulator of component A is a weak acid soluble in water, specifically citric acid or succinic acid, and its addition amount is such that the pH of the pH regulator solution is 1-2, and the mass ratio is not more than 3% of the weight of the filler in component A.

9. A long-lasting anti-aging high bonding strength elastic hybrid adhesive, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the long-lasting anti-aging, high bonding strength elastic hybrid adhesive according to claim 9 in the manufacture of power battery cells.

Citation Information

Patent Citations

  • Epoxy resin modified MS sealant

    CN109880569A

  • High-strength high-hardness epoxy modified MS sealant and preparation method thereof

    CN111732933A

  • High-strength high-hardness UV / moisture dual-curable MS adhesive and preparation method thereof

    CN112552870A

  • Acrylic acid modified MS sealant and preparation method thereof

    CN114672274A

  • Sealant as well as preparation method and application thereof

    CN115926711A